Type specimens of names in Bauhinia and Phanera (Fabaceae: Caesalpinioideae) at Central National Herbarium, Howrah (CAL) (Bangladesh Journal of Plant Taxonomy, 2017)
The types of the names in Bauhinia L. and Phanera Lour. at Central National Herbarium, Howrah (CAL) have been enumerated.Keywords: Fabaceae; Caesalpinioideae; Bauhinia; Phanera; Types; CAL.Bangladesh J. Plant Taxon. 24(1): 18, 2017 (June)